ACTUALISATION OF ISLAMIC EDUCATION FOR CHILDREN IN FAMILY LIFE IN RANGAS NEIGHBOURHOOD, RANGAS VILLAGE, MAJENE REGENCY - Dzulhaj, Nurfajriyah; Malli, Rusli; Sumiati, Sumiati (JICSA : Journal of Islamic Civilization in Southeast Asian, 2024)
Islamic education is the most important and important provision for children, and that's why parents have a responsibility to children in terms of providing teaching, especially Islamic religious education as a provision for children to welcome the future. Islamic religious education in the family environment should be well actualized because Islamic religious education is a strong initial foundation for children and families, especially parents have an important role in providing Islamic education to children, especially in today's modern era parents must pay extra attention to parenting and providing Islamic religious education. The obligation of parents to provide education to children is in line with the right of children to get education from their parents. This is explained in the 1945 Constitution in article 208 (1) "Everyone has the right to education and teaching. Education is the right of every citizen and is mandatory for citizens". Furthermore, this study aims to determine the actualization of Islamic education to children, the methods used in its application, and the challenges faced by parents. Using qualitative research methods with data sources in the form of parents in the Rangas neighborhood. The results of this study indicate that Islamic education is actualized by parents, namely; belief education, worship education, and moral education. Using four teaching methods including; the qishah (storytelling) method, hiwar (dialog) method, habituation method, method, and exemplary method. As well as various kinds of challenges faced, among others; children having difficulty accepting advice, children having their own opinions, and so on.